Archaeology of the land of the Bible - Mazar, Amihay, 1942-; Stern, Ephraim, 1934-; Meyers, Eric M; Chancey, Mark A (New York : Doubleday, 1990)
In volume 1, Israeli archaeologist Mazar (Institute of Archaeology, Hebrew U. in Jerusalem) introduces archaeological research in Israel and Jordan, and discusses its implications for our knowledge of the world of the Old Testament. He covers the period from the first permanent settlements to the destruction of the First Temple by Nebuchadnezzar and the Babylonian domination of the country. Volume 2 considers various artifacts unearthed in recent years and relates them to the Assyrian, Babylonian, and Persian periods in the Bible. Accompanied by photographs and illustrations of ancient relics ranging from household pottery to jewelry and sculpture. Volume 3 explores the archaeological record of the land of the Bible from its conquest by Alexander the Great in the fourth century BCE until the reign of the Roman Emperor Constantine in the fourth century CE. Focusing on the region's archaeology during the crucial Greco-Roman era, this book offers an overview of a tumultuous period in world history
[v. 1] 10,000-586 B.C.E. / by Amihai Mazar -- v. 2 The Assyrian, Babylonian, and Persian periods 732-332 B.C.E. / Ephraim Stern, 2007 -- v. 3 Alexander to Constantine / Eric M. Meyers, Mark A. Chancey, 2012
Includes bibliographical references and indexes
Keywords: Bible -- Antiquities; Palestine -- Antiquities